1976
DOI: 10.1007/bf00278892
|View full text |Cite
|
Sign up to set email alerts
|

Possible intrachromosomal duplication in a case of trisomy 9p

Abstract: A 5-year-old boy with multiple minor anomalies and mental retardation was found to have chromosomal condition of 46,XY,inv dup(9p) (pter leads to p13::p21 leads to p24::p13 leads to qter). The clinical features of the propositus fit well with those of trisomy 9p which have been established to be a clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…However, most of these reported duplications are due to malsegregation of chromosomes inherited from a parent with a reciprocal translocation involving chromosome 9, with relatively few pure 9p duplications arising de novo [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Bonaglia et al, 2002; Krepischi-Santos and Vianna-Morgante, 2003; Swinkels et al, 2008]. Despite varying sizes of duplicated chromosomal segments, there is a significant overlap in clinical features in duplication 9p syndrome, which is attributed to the terminal segment of 9p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these reported duplications are due to malsegregation of chromosomes inherited from a parent with a reciprocal translocation involving chromosome 9, with relatively few pure 9p duplications arising de novo [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Bonaglia et al, 2002; Krepischi-Santos and Vianna-Morgante, 2003; Swinkels et al, 2008]. Despite varying sizes of duplicated chromosomal segments, there is a significant overlap in clinical features in duplication 9p syndrome, which is attributed to the terminal segment of 9p.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these patients, the duplication 9p is a result of an abnormal chromosome segregation of a balanced translocation in one of the parents [Baccichetti and Tenconi, 1973; Wajntal et al, 1985]. De novo duplications of this chromosomal region have been previously described in approximately 15 patients [Chiyo et al, 1976; Baccichetti et al, 1979; Fryns et al, 1979; Motegi et al, 1985; Mattina et al, 1987; Haddad et al, 1996; Fujimoto et al, 1998; Tsezou et al, 2000; Krepischi-Santos and Vianna-Morgante, 2003]. Patients with partial trisomy of the short arm of chromosome 9 often display a wide spectrum of clinical symptoms including developmental delay, craniofacial abnormalities (bulbous nose, hypertelorism, downward-slanting palpebral fissures), limb abnormalities (short fingers and toes with small nails, fifth-finger clinodactyly) and skeletal malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases are associ- Figure 1 ated with de novo or familial translocations [Hoehn et al, 1971;Baccichetti and Tenconi, 1973;Penchaszadeh and Coco, 1974;Mason et al, 1975;Wajntal et al, 1985]. Only 10 cases with de novo 9p duplications have been described, mainly with direct duplications [Fryns et al, 1979;Cuoco et al, 1982;Motegi et al, 1985;Mattina et al, 1986;Phelan et al, 1993;Fujimoto et al, 1998], but some inverted duplications have also been reported [Chiyo et al, 1976;Baccichetti et al, 1979;Zadeh et al, 1981]. A single report of familial transmission of a dir dup (9) (p22p24) has been published [Haddad et al, 1996].…”
Section: Discussionmentioning
confidence: 93%
“…Most cases are due to unbalanced forms of either familial or sporadic translocations [Hoehn et al, 1971;Baccichetti and Tenconi, 1973;Penchaszadeh and Coco, 1974;Mason et al, 1975;Wajntal et al, 1985], but a few cases with duplications of 9p have also been described [Chiyo et al, 1976;Baccichetti et al, 1979;Fryns et al, 1979;Zadeh et al, 1981;Cuoco et al, 1982;Motegi et al, 1985;Mattina et al, 1986;Phelan et al, 1993;Haddad et al, 1996;Fujimoto et al, 1998]. …”
Section: Introductionmentioning
confidence: 96%
“…Almost 150 patients with partial or complete 9p trisomy have been reported, but most patients had an unbalanced translocation involving another chromosome [Young et al, 1982;Wilson et al, 1985]. Ten published cases involved a de novo duplication [Chiyo et al, 1976;Baccichetti et al, 1979;Fryns et al, 1979;Zadeh et al, 1981;Cuoco et al, 1982;Motegi et al, 1985;Mattina et al, 1987;Bussani Mastellone et al, 1991;Phelan et al, 1993;Fujimoto et al, 1998], and one case was a direct inherited duplication [Haddad et al, 1996] (Table I). Partial 9p duplication is a rare event, and breakpoints at 9pter including the telomeric repeated sequences as in our case were not reported.…”
Section: Discussionmentioning
confidence: 94%